5b-5-12b-9=

Simple and best practice solution for 5b-5-12b-9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b-5-12b-9= equation:


Simplifying
5b + -5 + -12b + -9 = 0

Reorder the terms:
-5 + -9 + 5b + -12b = 0

Combine like terms: -5 + -9 = -14
-14 + 5b + -12b = 0

Combine like terms: 5b + -12b = -7b
-14 + -7b = 0

Solving
-14 + -7b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -7b = 0 + 14

Combine like terms: -14 + 14 = 0
0 + -7b = 0 + 14
-7b = 0 + 14

Combine like terms: 0 + 14 = 14
-7b = 14

Divide each side by '-7'.
b = -2

Simplifying
b = -2

See similar equations:

| 20+8q-11=-12 | | 8x=30+5x | | 53-7x=2x+18 | | 4(x-3)=-2(x-4) | | ax-3b+7c=0 | | 12=10+12 | | ax-3b=7c | | -1(x+2)=5(x+1) | | 2x^2-3=-53 | | 5x^2=38x+16 | | -10-5x=5 | | 3(x-1)=4(x+2) | | -9-2x=17 | | -9-2x=16 | | 4y+10y=360+15-30y | | x+7=19-2x | | x+2x+3=x+15 | | 28+x=11 | | 3x+11=-4 | | 7x+15=-6 | | 10x-12+10=18+20 | | 3x+5+2x=100 | | y+32=13 | | 5t-7=11-t | | 8+17=9 | | -7x-12=44 | | x^2-3x=-0.5 | | 72+13= | | 3[3(4x-7)-4(2x-7)]=11x+25 | | 3s+5p=tp-5 | | 5[4+6(4x-2)]=6x-838 | | x^2-3x+2.25=1.75 |

Equations solver categories